Design and analysis of an OFDM-based orthogonal multilevel code-shifted differential chaos shift keying - Fadhil S. Hasan; Hayder F. Fahad (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In this paper, a new non-coherent chaos-based communication that combined orthogonal multilevel code-shifted differential chaos shift keying with orthogonal frequency division multiplexing named (OFDM-OMCS-DCSK) modulation system. New orthogonal chaotic signal sets are generated by hybrid gram-schmidt algorithm and walsh code function and used it to carry high data rate in the same time slot. The bandwidth efficiency of the OFDM-OMCS-DCSK system is comparing with conventional system. Also, the BER analytic expressions are derived under (AWGN) and multipath Rayleigh fading channels and comparing with the simulation results. Furthermore, the BER performance is compared with OFDM-DCSK to found that the proposed system has the best BER performance with high data rate feature.